Information Technology and the Concept of Crime in Cyber Space - Dusmatov Durbek Rustamjon ogli (Genius Journals, 2023)
In this article, the concepts of information technology and cybercrime are aimed at revealing the concepts of cybercrime, the implementation of countermeasures against them, and the division of cybercrime into groups
Keywords: Concept of cybercrime; similarities and differences between information technology and cybercrime; cross-border nature of cybercrime